Continuous Volatile Fatty Acid Production From Acid Brewery Spent Grain Leachate in Expanded Granular Sludge Bed Reactors - Castilla-Archilla, Juan; Heiberger, Jonas; Mills, Simon; Hilbig, Julia; Collins, Gavin; Lens, Piet N. L. (Frontiers in Sustainable Food Systems, 2021)
The production of volatile fatty acids (VFAs) in expanded granular sludge bed (EGSB) reactors using leachate from thermal diluted acid hydrolysis of brewery spent grain was evaluated. Partial inhibition of the anaerobic digestion process to induce VFA accumulation was achieved by applying a high organic loading rate (from 15.3 to 46.0 gCOD/(L·day)), and using a feed with an inlet concentration of 15 g/L total carbohydrates. Two EGSB reactors were operated under identical conditions, both inoculated with the same granular sludge. However, granular sludge in one reactor (R1) was subsequently disaggregated to flocculent sludge by a pH shock, whereas granules remained intact in the other reactor (R2). The hydraulic retention time (HRT) of both reactors was decreased from 36 to 24, 18 and 12 hours. The main fermented compounds were acetic acid, butyric acid, propionic acid and ethanol. Despite fluctuations between these products, their total concentration was quite stable throughout the trial at about 134.2 (± 27.8) and 141.1 (± 21.7) mmol/L respectively, for R1 and R2. Methane was detected at the beginning of the trial, and following some periods of instability in the granular sludge reactor (R2). The hydrogen yield increased as the HRT decreased. The highest VFA production was achieved in the granular sludge reactor at a 24 h HRT, corresponding to 120.4 (± 15.0) mmol/L of VFAs. This corresponded to an acidification level of 83.4 (± 5.9) g COD of VFA per total gram of soluble COD.